A Prefrontal-Hippocampal Comparator for Goal-Directed Behavior: The Intentional Self and Episodic Memory - Numan, Robert (Frontiers in Behavioral Neuroscience, 2015)
Abstract The hypothesis of this article is that the interactions between the prefrontal cortex and the hippocampus play a critical role in the modulation of goal-directed self-action and the strengthening of episodic memories. We describe various theories that model a comparator function for the hippocampus, and then elaborate the empirical evidence that supports these theories. One theory which describes a prefrontal-hippocampal comparator for voluntary action, is emphasized. Action plans are essential for successful goal-directed behavior, and are elaborated by the prefrontal cortex. When an action plan is initiated, the prefrontal cortex transmits an efference copy (or corollary discharge) to the hippocampus where it is stored as a working memory for the action plan (which includes the expected outcomes of the action plan). The hippocampus then serves as a response intention-response outcome working memory comparator. Hippocampal comparator function is enabled by the hippocampal theta rhythm allowing the hippocampus to compare expected action outcomes to actual action outcomes. If the expected and actual outcomes match, the hippocampus transmits a signal to prefrontal cortex which strengthens or consolidates the action plan. If a mismatch occurs, the hippocampus transmits an error signal to the prefrontal cortex which facilitates a reformulation of the action plan, fostering behavioral flexibility. The corollary discharge provides the self-referential component to the episodic memory, affording the personal and subjective experience of what behavior was carried out, when it was carried out, and in what context (where) it occurred. Such a perspective can be applied to episodic memory in humans, and episodic-like memory in subhuman animal species.